(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the migration of Turkestan intellectuals in the early twentieth century from historical, political, and social perspectives. The main causes of migration are identified as the colonial policies of the Russian Empire, Soviet-era repressions, and intellectual migration within the framework of the Jadid movement. The author divides this process into three main stages, analyzing its directions and consequences. Special attention is given to the activities of Turkestan intellectuals in Germany, Turkey, and France, highlighting their contribution to preserving national identity and promoting enlightenment ideas. The study concludes that this migration was a strategic effort aimed at preserving the nation’s intellectual potential and establishing the foundations of modern statehood.